A Qualitative Study Understanding How Mental Health Is Viewed Amongst South African Middle-adult Muslim Males - Razak, Tahiyya (The IIE, 2020)
Demonic possession, lack of faith and bad luck, these are some of ways mental health has been misconstrued in the Muslim community. The paramount influence that Islam has on how mental health is understood requires attention and rigours research. The focus of this research adopted a qualitative approach to researching how mental health is viewed amongst South African middle-adult Muslim males. Three participants fitted the specified sampling criteria and thereafter, a qualitative questionnaire was administered. Thematic analysis was employed to analyse the collected data and three themes emerged. The main theme identified was the stigmatization of mental health within the Muslim community. Historically, there has been stigmatization due to the misunderstanding of metal health. The findings that emerged was the tension between understanding mental health, treatment practices and acknowledging mental health. Therefore, further research would be required to understand how mental health is viewed in the South African Muslim community.
Keywords: Middle-adult; Males; Muslim community; Mental health; Perceptions; South Africa